PODER DE MERCADO DE LA COOPERATIVA DE TRANSPORTES “UNIÓN CARIAMANGA” Y SU INFLUENCIA EN LA COMPETENCIA Y CALIDAD DEL SERVICIO PRESTADO POR ESTA EMPRESA, EN LA TRANSPORTACIÓN INTERCANTONAL DE PASAJEROS DE LA PROVINCIA DE LOJA EN EL AÑO 2013 - Vega Coello, Cristian Armando (2015)
The market power of a firm can influence, restricting the competitive capacity of their rivals and also decreasing the quantity and quality of goods or services offered; In the province of Loja, almost half of the frequencies of intercantonal transport are offered by a single company, the “Union Cariamanga”, situation that could generate failures in the competition and quality of service. Therefore the general objective of this research is: Determine the influence of the market power of the “Union Cariamanga” Transport Cooperative, in the competition and quality of service provided by it, in the intercantonal passenger transportation in the province of Loja in the year 2013. For the present research was necessary the collaboration of the managers of the four intercantonal transport cooperatives; also, the manager of the “Reina del Cisne” bus station and of course of its users; the research process was developed in all cantons of the province and for its development was necessary the use of the inductive, statistical, analytical and descriptive methods, as well as techniques such as survey, interview and documentary analysis with their instruments as questionnaire and interview guide. The general conclusion we could reach is that “Unión Cariamanga” Transport Cooperative does not have the characteristics and necessary conditions to influence in market in the Loja province in the year 2013, but the intercantonal transport market in the province is highly concentrated, which does not allow the natural development of competition and generate that the quality of service offered by the cooperatives of this sector wasn´t the best. Key words: market power, intercantonal transport, competition, service quality, economic concentration, Unión Cariamanga.